Restructuring Family Life: Social Work Practice with Families Experiencing Socio-Psychological Problems - Amirah Putri Reza; Mia Aulina Lubis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze social work practices in restructuring the lives of families experiencing socio-psychological problems. The method used is library research, involving a review of various literature related to social work, family dynamics, and social interventions. The findings indicate that family problems require a comprehensive approach through assessment, assistance, and needs-based interventions. Social work practice plays an important role in helping families improve their social functioning, enhance communication, and build family resilience. Restructuring family life is a strategic effort to create sustainable social welfare.